Evidence based medicine: Teaching with clinical relevance in an undergraduate medical curriculum - Nowak, A.; Jacobs, Ian; Lake, F.; Jonas-Dwyer, D.; Carr, S. (ANZAME: The Association for Health Professional Education, 2010)
The practice of Evidence Based Medicine (EBM) enables clinicians to integrate the individual patient situation, clinical expertise, and the best available evidence for quality patient care. A pilot series of tutorials in which students were guided through the EBM process to answer clinical questions focused on a patient seen in a clinical attachment are highlighted.